2011
DOI: 10.1002/em.20690
|View full text |Cite
|
Sign up to set email alerts
|

Lower levels of oxidative DNA damage and apoptosis in lymphocytes from patients undergoing surgery with propofol anesthesia

Abstract: Propofol, which is widely used as an intravenous anesthetic, has a phenolic structure similar to that of α-tocopherol with antioxidant properties that could prevent genotoxicity and cytotoxicity in lymphocytes of anesthetized patients. The aims of this study were to evaluate oxidative DNA damage and apoptosis in lymphocytes and the expression of DNA repair genes in blood cells from patients undergoing elective surgery under anesthesia with propofol. Twenty healthy adults of both genders (18-50 years old) who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…In relation to genetic damage, propofol prevented DNA cleavage in peroxynitrite injury in primary astroglial cell cultures. 6 Although we have already observed a reduction of genetic lesions evaluated by formamidopyrimidine DNA glycosylase (FPG) sites during propofol anesthesia, 44 we did not detect a decrease in oxidized DNA using OGG1 when total IV anesthesia with propofol was administered. This could be explained by different types of oxidative damage recognized by OGG1 or FPG repair enzyme.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In relation to genetic damage, propofol prevented DNA cleavage in peroxynitrite injury in primary astroglial cell cultures. 6 Although we have already observed a reduction of genetic lesions evaluated by formamidopyrimidine DNA glycosylase (FPG) sites during propofol anesthesia, 44 we did not detect a decrease in oxidized DNA using OGG1 when total IV anesthesia with propofol was administered. This could be explained by different types of oxidative damage recognized by OGG1 or FPG repair enzyme.…”
Section: Discussionmentioning
confidence: 58%
“… 18 , 45 In a previous study, we reported a decrease of hydrogen peroxide-induced genotoxicity in lymphocytes as well as a reduction of apoptotic T helper cells collected from patients during surgical procedures with propofol anesthesia. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Genetic damage evaluation (basal DNA damage and oxidized bases) was conducted in lymphocytes that were isolated from freshly collected blood, and the comet assay was performed according to previously described protocols. 20,21 Briefly, cells were added to low-melting-point agarose at 37°C and set on slides, and the agarose was allowed to solidify. The slides were then im- The MN assay was performed on buccal epithelial cells that were collected by rubbing the inside of the subject's cheeks with a spatula, which was then placed in a tube containing PBS.…”
Section: Genotoxicity and Mutagenicity Assaysmentioning
confidence: 99%
“…Furthermore, small doses of propofol can be directly used to treat nausea and vomiting following surgery. Propofol can adjust the activity of cytotoxic T lymphocytes to increase their antitumor activity and immune regulation (12). In the present study, the anticancer effects of propofol on cell apoptosis of melanoma cells were investigated, and the underlying mechanism was investigated.…”
Section: Introductionmentioning
confidence: 99%